Anilox roller
By covering the outer surface of the anilox roller with a flexible material layer formed into grooves and raised structures, the serious wear of point-coating rollers is solved, the service life is extended, the cost is reduced, and the coating effect and operability are improved.
Patent Information
- Application Number
- CN202510001062.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
AI Technical Summary
In the existing lithium battery separator coating process, the contact between the dot coating roller and the anilox roller causes serious wear of the dot coating roller, which affects the coating effect and increases costs.
An anilox roller is designed with its outer surface covered with a layer of flexible material to form multiple grooves and protrusions arranged in an array, ensuring that the anilox roller and the dot coating roller operate in contact with each other at different linear speeds, reducing wear.
The service life of the dot coating roller is extended, the cost caused by frequent replacement of the dot coating roller is reduced, and the risk of impurities entering the slurry is reduced, and the coating effect and operability are improved.
Smart Images

Figure CN119771684A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery separators, and in particular relates to an anilox roller. Background Art
[0002] With the rapid update of electronic products and the rapid expansion of new energy electric vehicles in the market, lithium batteries, as an important energy storage device with high energy density and long life, are increasingly attracting the attention of producers and users. One of the core components of lithium batteries is the diaphragm, which can effectively isolate the positive and negative electrodes, prevent battery short circuits and electrolyte impregnation, thereby ensuring the safety and performance stability of lithium batteries. Compared with PP or PE base films, coating films generally have better high temperature stability, chemical stability, and higher mechanical strength and toughness. However, the coating process has a greater impact on the performance of the coating film. Therefore, the lithium battery diaphragm coating process is crucial to the performance and service life of lithium batteries.
[0003] With the continuous exploration of separator coating methods, a new coating method - matrix coating, has gradually come into the public eye. Because of its controllable coating point arrangement, controllable coating coverage, thickness and other advantages, it has gradually been applied to the manufacturing of new batteries.
[0004] However, because it is a new coating method, it has been applied in production practice for too short a time, and its process drawbacks have gradually been discovered. For example, the spot coating rollers used in this process are limited by the coating method. The spot coating rollers currently used are all made of flexible materials, while the anilox rollers (which play the role of transferring slurry) in contact with them are made of hard materials. During the contact between the two, the convex points of the spot coating roller cannot be guaranteed to fall 100% into the grooves of the anilox roller. Therefore, long-term operation will inevitably cause wear of the spot coating roller, resulting in poor coating effect. New spot coating rollers can only be replaced frequently, resulting in increased costs. Summary of the invention
[0005] In view of the shortcomings of the prior art, an object of the present invention is to provide an anilox roller. When the anilox roller is used in conjunction with a dot coating roller, the rotation speeds of the anilox roller and the dot coating roller are the same or different.
[0006] The purpose of the present invention is achieved through the following technical solutions.
[0007] A screen roller comprises: a roller body and a flexible material layer, wherein the outer surface of the roller body is cylindrical, the flexible material layer is formed into a ring shape and is attached to the circumferential surface of the roller body and is fixedly connected to the roller body, the outer surface of the flexible material layer is formed with a plurality of grooves arranged in an array, adjacent grooves are arranged at intervals, and the flexible material layer forms protrusions relative to the bottoms of the grooves between adjacent grooves, and the protrusions form a grid on the outer surface of the flexible material layer.
[0008] In the above technical solution, the roller body is a cavity.
[0009] In the above technical solution, the outer diameter of the roller body is 81-106 mm, and the wall thickness of the roller body is 3-10 mm.
[0010] In the above technical solution, the thickness of the flexible material layer is 2 to 5 mm.
[0011] In the above technical solution, the material of the flexible material layer is at least one of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), ethylene-propylene-diene terpolymer (EPDM), polyethylene-octene co-elastomer (POE), thermoplastic elastomer (TPE), and poly 2,6-dimethyl-1,4-phenylene ether (PPE).
[0012] In the above technical solution, the roller body is made of alloy steel.
[0013] In the above technical solution, the depth of each groove is 0.1 to 3 mm.
[0014] In the above technical solution, the grooves are arranged at equal intervals on the outer surface of the flexible material layer.
[0015] In the above technical solution, the cross-sectional shape of each groove along the circumferential surface of the roller body is one or more of a quadrilateral, a triangle and a hexagon.
[0016] In the above technical solution, the width of the protrusion is 100-200 μm.
[0017] A membrane coating system comprises an anilox roller and a dot coating roller, wherein the anilox roller is used for contacting slurry and transferring the slurry to the dot coating roller, and the dot coating roller is used for coating the membrane, and the rotation speeds of the anilox roller and the dot coating roller are the same or different.
[0018] Use of anilox rollers in reducing membrane defects.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The outer surface of the anilox roller of the present invention is a flexible material layer, so that the anilox roller and the spot coating roller can be in contact and run at different linear speeds without causing wear of the spot coating roller, thereby increasing the service life of the spot coating roller and reducing the cost caused by frequent replacement of the spot coating roller. Meanwhile, in the prior art, during the wear of the spot coating roller, the debris generated by the wear of the spot coating roller will be mixed into the slurry, resulting in an increase in impurities and contamination of the slurry. The present invention can reduce this risk to a great extent;
[0021] 2. In the prior art, in order to minimize the wear of the spot coating roller when using a metal anilox roller, the linear speeds of the metal anilox roller and the spot coating roller can only be kept consistent as much as possible, which means that when the amount of liquid carried by the metal anilox roller is constant, the adjustable range of the amount of slurry transferred by the spot coating roller is very small. However, when the amount of liquid carried by the anilox roller is constant, the present invention can adjust the amount of slurry transferred by the spot coating roller by adjusting the linear speed ratio of the spot coating roller to the anilox roller, thereby achieving the purpose of adjusting the coating effect, improving operability, and broadening process conditions;
[0022] 3. The outer surface of the anilox roller of the present invention is a flexible material layer, so that the shape of the convex points of the dot coating roller is well maintained, the consistency of the coating points on the diaphragm is good, and the performance of the diaphragm is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a cross-sectional view of the anilox roller in Example 1;
[0024] Figure 2 It is a partial schematic diagram of the outer surface of the anilox roller in Example 1;
[0025] Figure 3 This is the appearance of the diaphragm in Example 3;
[0026] Figure 4 The thickness test results in Example 3;
[0027] Figure 5 This is the weight test result in Example 3.
[0028] Among them, 1: flexible material layer, 2: roller body, 3: groove, 4: protrusion. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0030] The base film used in the following implementation is a PE film with a thickness of 9 μm, and the width of the base film is larger than the coating width of the dot coating roller.
[0031] The preparation method of the conventional spot coating slurry in the following embodiment is as follows: PVDF powder, pure water and dispersant are mixed, blended in a planetary stirring device for 60 minutes until uniform (rotation speed is 2000r / min, revolution speed is 40r / min), sanded for 15 minutes, and then thickener, binder and wetting agent are added, and blended in a planetary stirring device for 25 minutes until uniform (rotation speed is 1300r / min, revolution speed is 40r / min) to obtain a conventional spot coating slurry, and the ratio of dispersant, wetting agent, PVDF powder, pure water, thickener and binder is 0.5:2.5:16:47:16:18 by mass. The binder is styrene-butyl methacrylate, the dispersant is ammonium polyacrylate, the thickener is hydroxymethyl cellulose, and the wetting agent is polyoxyethylene ether.
[0032] Example 1
[0033] like Figure 1 As shown, a screen roller comprises: a roller body 2 and a flexible material layer 1, the roller body 2 is a cavity, the outer surface of the roller body 2 is a cylindrical shape, the flexible material layer 1 is formed into a ring and attached to the circumferential surface of the roller body 2 and fixedly connected to the roller body 2, and the outer surface of the flexible material layer 1 is formed as shown in Figure 2 The array shown shows multiple grooves 3 (grooves 3 are laser engraved), and the grooves 3 are arranged at equal intervals on the outer surface of the flexible material layer 1. The outer diameter of the roller body 2 is 94 mm, the wall thickness of the roller body 2 is 5 mm, the thickness of the flexible material layer 1 is 3 mm, the material of the flexible material layer 1 is TPE-U, and the material of the roller body 2 is alloy steel.
[0034] The depth of each groove 3 is 2 mm. The cross-section of each groove 3 along the circumferential surface of the roller body 2 is in a rhombus shape. Adjacent grooves 3 are arranged at intervals, and the flexible material layer 1 forms protrusions 4 relative to the bottom of the grooves 3 between adjacent grooves 3, and the protrusions 4 form a grid on the outer surface of the flexible material layer 1. The width of the protrusions 4 is 200 μm.
[0035] Example 2
[0036] A conventional anilox roller comprises: a roller body, the roller body is a cavity, the outer surface of the roller body is cylindrical, the outer surface of the roller body is provided with a plurality of grooves arranged in an array (the grooves are laser engraved), the arrangement array of the grooves on the roller body in this embodiment is the same as the arrangement array of the grooves 3 on the flexible material layer 1 in Example 1, the outer diameter of the roller body in this embodiment is 94 mm, the wall thickness of the roller body is 5 mm, and the material of the roller body is alloy steel. The depth of each groove in this embodiment is 2 mm. The cross-section shape of all the grooves along the circumferential surface of the roller body is a rhombus. The interval between the side lengths of each two adjacent grooves (equivalent to the width of the "protrusion 4" in Example 1) is 200 μm.
[0037] Example 3
[0038] The anilox roller of Example 1 and the conventional anilox roller of Example 2 were used on the same coating machine to coat the conventional dot coating slurry on the base film to verify the wear of the dot coating roller:
[0039] Prepare two dot coating rollers a and b of the same material, model and specification, and two barrels of 30 kg of conventional dot coating slurry. Weigh the two dot coating rollers before coating. The weight of dot coating roller a is 3100 g, and the weight of dot coating roller b is 3103 g.
[0040] The conventional anilox roller of Example 2 is used in combination with the dot coating roller a, and the anilox roller of Example 1 is used in combination with the dot coating roller b (the matching method of the anilox roller and the dot coating roller b is conventional, as described in CN116174260A). Figure 1 As shown), during coating, the speed of the coating machine is set to 100 m / min, and the linear speeds of the anilox roller of Example 1, the conventional anilox roller of Example 2, the dot coating roller a and the dot coating roller b are all 100 m / min,
[0041] First, take a bucket of conventional spot coating slurry with a mass of 30 kg, and use the conventional anilox roller and spot coating roller a of Example 2 for coating, and the coating length is 100,000 meters; then take another bucket of conventional spot coating slurry with a mass of 30 kg, and use the anilox roller and spot coating roller b of Example 1 for coating, and the coating length is 100,000 meters.
[0042] After coating, the dot coating roller a and the dot coating roller b were ultrasonically cleaned (ultrasonic at a frequency of 30 kHz for 10 minutes) and dried. The weight of the dot coating roller a was 3078 g, the weight of the dot coating roller b was 3099 g, the wear loss of the dot coating roller a was 22 g, and the wear loss of the dot coating roller b was 4 g. The anilox roller in Example 1 has an obvious effect on improving the wear of the dot coating roller.
[0043] Check the defects of the diaphragms coated by the dot coating roller a and the dot coating roller b respectively to see if there are impurities and identify whether they are particles from the dot coating roller. Figure 3 As shown, the number of impurity defects in the diaphragm coated by the spot coating roller a is 23, and the number of impurity defects in the diaphragm coated by the spot coating roller b is 1, which indicates that the spot coating using the anilox roller of Example 1 can effectively reduce the impurity defects caused by the wear of the spot coating roller.
[0044] Samples were taken from the 99000m-100000m section of the diaphragm coated by the spot coating roller a and the spot coating roller b, respectively, to test the uniformity of the diaphragm thickness and the uniformity of the diaphragm weight, wherein, thickness test: 10 coating films were taken horizontally from the diaphragms coated by the spot coating roller a and the spot coating roller b, 10 test points were tested on each coating film (the 10 test points of each coating film were tested at the same position), and the thickness of each test point was obtained, and the thickness unit was μm; weight test: 10 coating films were taken horizontally from the diaphragms coated by the spot coating roller a and the spot coating roller b, 3 test areas were tested on each coating film (the area of each test area was the same), and the weight of each test area (the weight of the diaphragm per square meter) was obtained, and the weight unit was g / ㎡. The thickness test results are as follows: Figure 4 As shown ( Figure 4 The unit of the vertical axis is μm), and the weight test results are as follows Figure 5 As shown ( Figure 5 The unit of the vertical axis is g / ㎡).
[0045] Depend on Figure 4 and Figure 5 It can be seen intuitively that in the 99000m-100000m section, the dot coating roller b ( Figure 4 and Figure 5 The uniformity of the thickness and weight of the diaphragm obtained by the "b roller" is better than that of the dot coating roller a ( Figure 4 and Figure 5 The anilox roller of Example 1 can improve the coating effect.
[0046] Example 4
[0047] Prepare two dot coating rollers c and d with the same material, model and specification, and set up the first and second groups of experiments.
[0048] The first group: the conventional anilox roller of Example 2 was used in combination with the dot coating roller d, and conventional dot coating slurry was used for coating on the coater: the speed of the coater was set to 100 m / min, the linear speeds of the dot coating roller d and the conventional anilox roller were each 100 m / min, the coverage was set to 20%, and 500 m of coating was performed.
[0049] The second group: the anilox roller of Example 1 was used in combination with a spot coating roller c (the spot coating roller c weighed 3150 g before coating), and conventional spot coating slurry was used for coating on a coater to verify the coating effect when the speed of the coater, the linear speed of the spot coating roller c and the linear speed of the anilox roller were the same and different: during the coating process, the linear speed of the spot coating roller c and the speed of the coater were always maintained at 100 m / min, and the linear speeds of the anilox roller were set to 50 m / min, 60 m / min, 70 m / min, 80 m / min, 90 m / min, 100 m / min, 110 m / min, 120 m / min, 130 m / min, 140 m / min and 150 m / min, respectively, the coverage was set to 20%, and 500 m was coated at each linear speed of the anilox roller.
[0050] After coating, the coating thickness (membrane thickness-base film thickness) and coating amount (weight of coating on each square meter of membrane) of the membrane coated at the linear speed of each anilox roller in the second group were tested. The test results are shown in Table 1. It can be seen from Table 1 that when the linear speed of the dot coating roller c is kept unchanged, the coating thickness and coating amount are increased after the linear speed of the anilox roller is increased.
[0051] In the prior art, the speed of the conventional anilox roller must be consistent with that of the spot coating roller, otherwise the spot coating roller will be worn out once the two come into contact. Compared with the conventional anilox roller used for spot coating, which can only keep the same linear speed as the spot coating roller, the present invention broadens the process conditions of the equipment and makes the operation simpler.
[0052] Table 1
[0053]
[0054] After coating, the coating thickness and coating amount of the first group of coated diaphragms were tested. The test results are shown in Table 2.
[0055] Table 2
[0056]
[0057] After coating, the spot coating roller c was ultrasonically cleaned (at a frequency of 30 kHz for 10 minutes) and dried. The weight of the spot coating roller c was 3148 g. After coating, the spot coating roller c lost 2 g of weight, indicating that the degree of wear of the spot coating roller was smaller on the basis of broadening the process conditions.
[0058] While ensuring normal liquid carrying, the present invention can also meet the requirement that the contact between the anilox roller and the dot coating roller is soft contact. Even if the convex points of the dot coating roller contact the anilox roller, the dot coating roller will not be damaged, thereby increasing the service life of the dot coating roller. During operation, the anilox roller and the dot coating roller can work at different linear speeds, thereby broadening the process conditions and greatly improving the adjustability of the equipment.
[0059] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. An anilox roller, characterized in that: include: A roller body (2) and a flexible material layer (1), wherein the outer surface of the roller body (2) is cylindrical, the flexible material layer (1) is formed into a ring and adheres to the circumferential surface of the roller body (2) and is fixedly connected to the roller body (2), the outer surface of the flexible material layer (1) is formed with a plurality of grooves (3) arranged in an array, adjacent grooves (3) are arranged at intervals, and between adjacent grooves (3), the flexible material layer (1) forms protrusions (4) relative to the bottoms of the grooves (3), and the protrusions (4) form a grid on the outer surface of the flexible material layer (1).
2. The anilox roller according to claim 1, characterized in that: The roller body (2) is a cavity.
3. The anilox roller according to claim 1, characterized in that: The outer diameter of the roller body (2) is 81 to 106 mm, and the wall thickness of the roller body (2) is 3 to 10 mm.
4. The anilox roller according to claim 1, characterized in that: The thickness of the flexible material layer (1) is 2 to 5 mm.
5. The anilox roller according to claim 4, characterized in that: The material of the flexible material layer (1) is at least one of styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, ethylene-propylene-diene terpolymer, polyethylene-octene co-elastomer, thermoplastic elastomer, and poly-2,6-dimethyl-1,4-phenylene ether.
6. The anilox roller according to claim 1, characterized in that: The depth of each groove (3) is 0.1-3 mm.
7. The anilox roller according to claim 6, characterized in that: The grooves (3) are arranged at equal intervals on the outer surface of the flexible material layer (1).
8. The anilox roller according to claim 7, characterized in that: The cross-sectional shape of each groove (3) along the circumferential surface of the roller body (2) is one or more of a quadrilateral, a triangle and a hexagon.
9. The anilox roller according to claim 1, characterized in that: The width of the protrusion (4) is 100 to 200 μm.
10. Use of the anilox roller according to claim 1 in reducing diaphragm defects.
Citation Information
Patent Citations
Material box device capable of changing coating width at will
CN116174260A